Language choice patterns of multilingual speakers in Sebuyau - Norahim, Norazuna; Wan Kahar, Sharifah Aishah; Hassan, Salbia (Centre for Academic Information Services (CAIS), 2010)
This paper reports preliminary results of an on-going research project undertaken to study the language choice patterns of multilingual communities in Sebuyau, a small coastal town situated at the border between Sri Aman and Simunjan. The research is part of a bigger project which examines language contact and multilingual communities in the south-western region of Sarawak i.e. in the district of Lundu, Sebuyau and Simunjan. In language contact situations, it is not languages that come into contact but speakers of the languages. Therefore, language attitude (e.g. perceptions towards each other’s language and own language), and the link between language and identity are crucial factors that will influence language choice (Appel & Musyken, 1987; Fishman, 1977; Grosjean, 1982; Norazuna, 2009; c.f. Sercombe, 2000). Data for this paper were collected through in-depth interview with the help of a questionnaire. In addition to the questionnaire, general observation of language choice behaviour of the Sebuyau in various social situations was conducted. The results suggest, among others, that the younger generation Iban are accommodating to the language of their Malay interlocutors in interaction. This change in norms of language use in Malay-Iban interaction may be also reflect attitudes towards languages.